2011
DOI: 10.1007/s00420-011-0616-9
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure levels to benzene in Italy: findings from a national database

Abstract: Occupational benzene exposure is still widespread in many different industries, and proactive measures are needed to reduce its impact on the workers' health. The potential of occupational exposure databases as a source of data for exposure assessment is confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…The main limitations of the SIREP database are the inhomogeneous territorial coverage and the underrepresentation of some economical activities, as already underlined in previous studies (27,28). Data collection and reporting for the SIREP system is under the responsibility of the employer, and we observed that the number of exposure measurements differed by industrial sector and firm size.…”
Section: Discussionmentioning
confidence: 59%
“…The main limitations of the SIREP database are the inhomogeneous territorial coverage and the underrepresentation of some economical activities, as already underlined in previous studies (27,28). Data collection and reporting for the SIREP system is under the responsibility of the employer, and we observed that the number of exposure measurements differed by industrial sector and firm size.…”
Section: Discussionmentioning
confidence: 59%
“…The main limitations of SIREP database are the inhomogeneous territorial coverage and the under-representation of some economical activities, as already underlined in previous studies [ 15 , 17 , 23 ]. Data collection and reporting for the SIREP database are under the responsibility of the employer, and we observed that the number of exposure measurements differed by industrial sector and workforce size.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the SIREP exposure surveillance system covers a large part of the industrial sectors entailing carcinogenic exposure risk. Weaknesses and strengths of the SIREP system have been extensively described elsewhere . In brief, data collection and selection of analytic/sampling method are under the responsibility of the employer, some potential factors affecting Ni air concentrations are not always reported (eg, environmental conditions or control measures), and the number of exposure measurements are not evenly distributed among industrial sectors and by firm size (eg, small firms results underreported).…”
Section: Discussionmentioning
confidence: 99%